The effectiveness of using Tellagami software to raise awareness of the Omani historical effects of eleventh graders - Al-Ghawi, Zouwaina Khalaf Mahfood; Al-Salmi, Hamad Suleiman Salem (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to reveal the effectiveness of using the Tellagami program in awareness the historical effects of Oman among eleventh grade students, where the researcher used the quasi-experimental method, for a sample of (60) female students. For basic education school (10-12). The sample was divided into two groups, the experimental group included (31) students who studied Omani historical monuments through the Tellagami program, and the control group included (29) students studied in the instructive way, and the equivalence of the two groups was verified through the tribal application of the Omani archaeological knowledge test, and measures of attitudes and behavior toward These effects. The researcher used three tools to collect data represented in testing the Omani archaeological knowledge consisting of (30) multiple-choice questions, and the scale of trends toward Omani historical monuments consisting of (20) questions distributed on (4) axes, and the behavior scale toward Omani historical monuments consisting of (13) questions, divided into (2) axes. The validity of the tools (both apparent and in-kind) was confirmed by a group of arbitrators, and its stability in internal consistency was measured by the Alpha Cronbach laboratory, and the stability factor for the Omani archaeological knowledge test reached (.62), while the measure of trends towards Omani historical monuments (.82). As for the behavior scale towards the Omani historical monuments, it reached (.70). The results showed statistically significant differences at (α = 0.05) between the mean of the two study samples in examining the knowledge, trends, and behavior of Omani historical monuments, as well as with regard to the level of general archaeological awareness in favor of the experimental group, and in light of these results the researcher recommended using the Tellagami program in teaching a subject Social Studies.